Characteristics of Romanian Travel Bloggers and Generated Content During COVID-19 - Briciu, Victor-Alexandru; Briciu, Arabela; Bularca, Maria Cristina; Dogaru, Georgiana (Springer, 2024)
Tourism plays a vital role in the global economy and its promotion relies on a variety of methods, including advertising, social media, and blogging. Tradi-tional travel writing has evolved into digital platforms such as blogs, micro-blogs, and travel apps, changing the way travellers document their journeys. This paper examines the phenomenon of travel blogging and its impact on the tourism industry, focusing on Romanian travel bloggers. We used content analysis to explore our research objectives: to understand the demographics of bloggers, to explore their travel interests, to analyse the topics covered, and to assess the effectiveness of travel blogs. This is particularly important given the challenges facing the tourism industry during the pandemic. In addition, our findings highlight the importance of travel-related blog posts, such as those discussing travel conditions and restrictions during the pandemic. These findings are valuable in both stable and disrupted travel industry contexts. In conclusion, this study reveals the evolving role of travel blogs and their importance in destination development and highlights the adaptability and relevance of travel blogs in different tourism scenarios.